Police administration - Gaines, Larry K.; Worrall, John L. (Delmar, 2012)
Offers an introduction to police administration for academic courses and for practitioners preparing for a promotional exam. This book allows students to understand key issues such as conflict resolution, human resources, budgeting and collective bargaining.